Appendices to record of evidence [electronic resource] : appendix "A", pleadings, appendix "B", exhibits. - Bering Sea Claims Commission.; United States.; Great Britain. ([Washington? : G.P.O.?, 1897)
Part of a CIHM set. For individual microfiches in this set see CIHM microfiche nos. 14456-14461. At head of title: Behring Sea Claims Commission. "Vol. III." Electronic reproduction. Mode of access: Internet. 44